AUTHENTIC ASSESSMENT IN AI-ENHANCED TESOL: A CONCEPTUAL INTRODUCTION - Dilnoza Usmanova (TADQIQOTLAR, 2025)
This paper introduces a conceptual foundation for integrating authentic language assessment principles with artificial intelligence technologies in TESOL. We examine the fundamental tensions between communicative language teaching and automated assessment systems, identifying key challenges and opportunities. By establishing a theoretical bridge between these domains, we provide language educators with a framework for evaluating and implementing AI assessment tools while maintaining pedagogical integrity.